Analysis of the Role of Algorithms in the Analysis of Organic Molecular Structures: A Study of Formal Charges and Their Reactivity - Muhali, Muhali; Hulyadi, Hulyadi; Gargazi, Gargazi; Azmi, Irham; Bayani, Faizul (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
This study aims to identify students' competency in understanding the formal charge and reactivity of organic molecules through algorithm-based learning and mathematical formulations. A quasi-experimental pretest–posttest design was used with Chemistry Education students who had taken the topic of chemical bonding and Lewis structures. Essay and multiple-choice tests were used to measure the accuracy of Lewis structures, formal charge calculations, charge symbol interpretation, and reactivity predictions. The pretest results showed an average student score of 32.4, while the posttest score increased to 74.1, with an N-gain of 0.62 (moderate–high category). Students showed significant improvement in identifying reactivity centers (electrophilic/nucleophilic) and linking charge distribution to structural stability. The application of algorithms also strengthened their ability to visualize electronic structures, particularly in the context of sp3and sp3 hybridization. Computational chemistry simulations helped students develop stronger symbolic and predictive representations of chemical reactions. This study concludes that the integration of algorithms and symbolic approaches in learning effectively improves students' conceptual and computational literacy in organic chemistry.